Analysis of lightning occurence in Zambia - Nyambe, Silumelume H.; Lubasi, Foster Chileshe; Gomes, Chandima; Gomes, Ashen (IEEE (IEEE Xplore), 2014)
This paper presents analysis of human observations on thunder days in five regional centers in Zambia. The regions covered are specifically of interest to aviation industry. The variation pattern of monthly thunder days show that the lightning activity has well-detectable oscillatory pattern over the year. However, the pattern varies from region to region thus, as a single country Zambia experiences lightning almost throughout the year. We strongly recommend the installation of automated lightning detection system in the country to provide more accurate lightning ground flash and cloud flash density mapping. Such information will play a vital role in lightning safety and protection planning.